2013
DOI: 10.1111/ctr.12272
|View full text |Cite
|
Sign up to set email alerts
|

Organ allocation in pediatric renal transplants: is there an optimal donor?

Abstract: The 2005 revised allocation scheme for pediatric renal transplantation made the decision of whether to transplant an available living-donor (LD) kidney or use a deceased-donor (DD) kidney controversial. The aim of this study was to examine kidney allograft utilization, sensitization, and outcomes of pediatric transplant recipients. Between January 2000 and December 2009, 91 consecutive pediatric kidney recipients (<20 yr) were transplanted. The LD (n = 38) and DD (n = 53) groups were similar in age, gender, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…If available, a LD is generally considered the best donor option with multiple studies demonstrating increased graft and recipient survival and better quality of life when compared to DD transplantation . As LDs are often biologically related to the pediatric recipient, HLA matching likely plays an important role in this outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If available, a LD is generally considered the best donor option with multiple studies demonstrating increased graft and recipient survival and better quality of life when compared to DD transplantation . As LDs are often biologically related to the pediatric recipient, HLA matching likely plays an important role in this outcome.…”
Section: Introductionmentioning
confidence: 99%
“…If available, a LD is generally considered the best donor option with multiple studies demonstrating increased graft and recipient survival and better quality of life when compared to DD transplantation. [7][8][9][10] As LDs are often biologically related to the pediatric recipient, HLA matching likely plays an important role in this outcome. However, whether this survival benefit is preserved with increasing age difference between the donor and the recipient in LD transplants is unknown.…”
mentioning
confidence: 99%
“…Occurrence of graft loss in the NPKT group was 12 months faster than that seen in the PKT group. The population studied here presented no difference in graft survival according to donor type; however, Pitt et al [3] found a superior graft survival in a living donor group. In the past 10 years, graft and patient survival rates have been compared between recipients of PKT and those of NPKT in different studies, and the outcomes have been shown to be comparable or even better for PKT [4e7].…”
Section: Discussionmentioning
confidence: 46%
“…Other reports have already found statistically significant longer graft survivals in pediatric recipients of grafts from living versus deceased donors [20][21][22] . On the other hand, in a model of GFR prognosis after pediatric kidney transplantation, Pape et al [23] found that donation from living donors did not correspondingly improve the prediction of GFR.…”
Section: Discussionmentioning
confidence: 85%